Distribution of Soil Extracellular Enzymatic, Microbial, and Biological Functions in the C and N-Cycle Pathways Along a Forest Altitudinal Gradient - Bayranvand, Mohammad; Akbarinia, Moslem; Salehi Jouzani, Gholamreza; Gharechahi, Javad; Baldrian, Petr (Frontiers in Microbiology, 2021)
The diverse chemical, biological and microbial properties of litter and organic matter in forest soil along an altitudinal gradient are potentially important for nutrient cycling. In the present study, we sought to evaluate soil chemical, biological, microbial and enzymatic characteristics at four altitude levels (0, 500, 1000 and 1500 m) in northern Iran to characterize nutrient cycling in forest soils. The results showed that carbon (C) and nitrogen (N) turnover change with altitude along with microbial properties and enzyme activity. At the lowest altitude with mixed forest and no beech trees, the higher content of N in litter and soil, higher pH and microbial biomass nitrogen (MBN), and the greater activities of aminopeptidases affected soil N cycling. At elevations above 1000 m, where beech is the dominant tree species, the higher activities of cellobiohydrolase, arylsulfatase, β-xylosidase, β-galactosidase, endoglucanase, endoxylanase and manganese peroxidase coincided with higher basal respiration (BR), substrate-induced respiration (SIR), and microbial biomass carbon (MBC) and thus favoured conditions for microbial entropy and C turnover. The low N content and high C/N ratio at 500 m altitude were associated with the lowest microbial and enzyme activities. Our results support the view that the plain forest with mixed trees (without beech) had higher litter quality and soil fertility, while forest dominated by beech trees had the potential to store higher C and can potentially better mitigate global warming.